Trends in drinking habits among adolescents in the Baltic countries over the period of transition: HBSC survey results, 1993-2002 - Maser Mai; Sumskas Linas; Zaborskis Apolinaras; Pudule Iveta (BMC, 2006)
Abstract Background The Baltic countries - Estonia, Latvia, and Lithuania - are considered to be an example of regional homogeneity over the period of transition. The World Health Organization cross-national study on Health Behavior in School-aged Children (HBSC) allows a comparison and time trends analysis of behavioral patterns among adolescents in this region. The aim of this study was to estimate the prevalence and trends of alcohol consumption and drunkenness among adolescents of Estonia, Latvia, and Lithuania in 1993/94, 1997/98, and 2001/02. Methods Representative samples of 5286 boys and 6485 girls aged 15 from Estonia, Latvia, and Lithuania were surveyed in 1993/94, 1997/98, and 2001/02 school-year within the framework of HBSC study. The standardized survey methods were applied. The research focused on the following outcome variables: i) frequency of drinking beer, wine, and spirits; and ii) frequency of drunkenness. The same wording of questions on the consumption of alcohol was retained in each survey. Results Beer was the most frequently used alcoholic beverage across the Baltic countries among adolescents. The rate of weekly drinking of any alcoholic beverage increased considerably during the eight years of observation, especially among Estonian and Lithuanian students. In 2001/02, 25% of boys and 12.5% of girls have reported drinking alcohol at least weekly. The rate of regular alcohol drinking was two times higher in boys, while irregular drinking was more prevalent in girls. Two or more episodes of drunkenness in the lifespan were reported by 30% of boys and 15% of girls in 1993/94 and by 52% of boys and 36% of girls in 2001/02. The use of alcoholic beverages was related to the perceived family wealth: the students from the families perceived by them as wealthy were more likely to drink weekly as compared to the students from the families perceived by them as not wealthy. Conclusion Over the period between 1993 and 2002 the prevalence of alcohol consumption among adolescents increased considerably across the Baltic countries. The efforts of dealing with this problem should employ a combination of measures, including the strategies relevant for the period of transition.